Can for-profit organizations practice religion?: theorizing faith integration in business - Lee, Min-Dong Paul (Journal of management, spirituality & religion, 2025)
This research explores how for-profit organizations integrate faith, a previously understudied area. Traditionally, businesses were seen as exclusively profit- driven and incapable of faith expression. A recent US Supreme Court case, however, sheds new light on how businesses run by religiously motivated leadership can creatively integrate and express faith. Based on five indepth case studies of faith-based businesses across five states, this study examines how faith is understood and experienced by the organizations' internal stakeholders. The findings from the thematic analysis of the data reveal three distinct dimensions of faith recognized by company stakeholders: embodied, operationalized, and internalized.